MANAJEMEN ISLAMI PERSPEKTIF AL-QUR’AN - zainarti zainarti (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2014)
Theoriesandconcepts management in use todayare actuallynot newinIslamicperspective. Themanagementhas beenthere at leastwhenGodcreated theuniverse and its contents. Management elementshad been exist in creaturing the nature. WhenProphetAdamascaliph leadthe universehasto implementthe elementsof themanagement. Managementin Islamis an activity, processesand procedurestoachievethe goal. Workbyeachjobto the fullest. Sotogethernessandthe end goalbeingthe main focus